Meet the Expert Tim O'Reilly on What's Wrong with Silicon Valley? - O'Reilly, Tim (O'Reilly Media, Inc., 2020)
The recent implosion of WeWork and the underperformance of Uber as a public company relative to its inflated pre-IPO expectations are just the tip of the iceberg. Is something wrong with the Silicon Valley funding model and its reliance on venture capital? Is it about to lead to another bust, or can we still find our way to more sustainable tech businesses and investments? In this special conversation, Tim O'Reilly covers why moving fast and breaking things is usually not the best strategy and how emulating the tortoise rather than the hare can lead to business success and building more value over time. Recorded on January 22, 2020. See the original event page for resources for further learning or watch recordings of other past events . O'Reilly Meet the Expert explores emerging business and technology topics and ideas through a series of one-hour interactive events. You'll engage in a live conversation with experts, sharing your questions and ideas while hearing their unique perspectives, insights, fears, and predictions.
Online resource; Title from title screen (viewed March 6, 2020)
Keywords: Internet videos; Streaming video; Vidéos sur Internet; Vidéo en continu; streaming video; Electronic videos